2017
DOI: 10.1007/s11440-017-0620-7
|View full text |Cite
|
Sign up to set email alerts
|

Tensile strength of large-scale incipient rock joints: a laboratory investigation

Abstract: In this paper, a testing methodology was developed in the laboratory to measure the tensile strength of large-scale incipient rock joints. In the test, an expansive grout was used to develop the tensile force. Each test comprises two phases: Phase i test and Phase ii test. The Phase i test identified sample failure time, while the Phase ii test measured the corresponding tensile force arising from the expansive grout. Ostensibly homogeneous rock samples without incipient joints were firstly tested to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 34 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…To better understand the swaying motion, we perform modal analysis (following Chopra, 2012, Chapter 17), using the elastic properties of the rock mass and geometry of the pillar. A complete analysis should account for intrinsic properties of elasticity, Poisson ratio, density, contact continuity at the base (Elmo et al, 2018) and incipient discontinuity tensile strength (Shang et al, 2018). These parameters vary naturally between rock masses and often are difficult to assess from surface mapping.…”
Section: Establishing the Suitability Of Pbr Methodology As A Uniformmentioning
confidence: 99%
See 2 more Smart Citations
“…To better understand the swaying motion, we perform modal analysis (following Chopra, 2012, Chapter 17), using the elastic properties of the rock mass and geometry of the pillar. A complete analysis should account for intrinsic properties of elasticity, Poisson ratio, density, contact continuity at the base (Elmo et al, 2018) and incipient discontinuity tensile strength (Shang et al, 2018). These parameters vary naturally between rock masses and often are difficult to assess from surface mapping.…”
Section: Establishing the Suitability Of Pbr Methodology As A Uniformmentioning
confidence: 99%
“…(e.g., Shang et al, 2018) this scenario suggests that for median spectral acceleration basal detachment is probable. For the M7.5 scenario and similar tensile strength assumption, the basal tensile stresses are below the incipient strength for the median spectral acceleration and marginally above the incipient strength lower bound for the single standard deviation value.…”
Section: 1029/2019jb019269mentioning
confidence: 96%
See 1 more Smart Citation
“…Through these studies, it has been observed that under the load conditions, the pre-existing crack is at the origin of the appearance and the propagation of the majority of the new cracks which transform into rock bridges. The existence of relatively small rock bridges at the discontinuities greatly increases their strength [24,25,26] which must first be broken before a rupture can take place.The above-mentioned studies also pointed out that, the propagation of cracks within a rock was a complex phenomenon and depended on the rock composition and the properties (geometry/ shape, orientation, and size) of the pre-existing cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Rock discontinuities are fundamentally important to most rock engineering projects [2]. Shang et al addressed the issue of tensile strength of incipient discontinuities in rock and presented results from a laboratory test programme to quantify this parameter [3,4]. Xiao et al studied the mechanical and deformation behaviors of the fractured rock-like material with one single fissure under the conventional triaxial compression [5].…”
Section: Introductionmentioning
confidence: 99%